Chronic Postoperative Mycobacterium gordonae Endophthalmitis in a Patient with Phakic Intraocular Lens. (23rd August 2013) - Couto, Cristobal; Rossetti, Silvia; Schlaen, Ariel; Hurtado, Erika; D'Alessandro, Leonardo; Goldstein, Debra A.
Abstract: Methods : Case description of a 34 year old woman with chronic granulomatous anterior uveitis following implantation of a phakic anterior chamber intraocular lens (IOL). Aqueous humor was processed for bacterial, fungal culture, and PCR analysis. Results : PCR for 16S ribosomal RNA universal primers was positive and Southern-blot for Propionibacterium spp was negative. Panfungal PCR was negative. Growth of a pigmented yellow colony was detected on Lowenstein-Jensen medium. The isolate was subsequently identified as Mycobacterium gordonae. The patient was treated for atypical mycobacteria as well as an intracameral injection of moxifloxacin, with resolution of inflammation and improvement in visual acuity. Conclusions : This is the first reported case of Mycobacterium gordonae chronic postoperative endophthalmitis, and of chronic endophthalmitis following phakic IOL surgery. PCR and cultures were invaluable in making the diagnosis.